Career Guidance and Counseling for Learner with Disabilities: Career Awareness, Career Exploration, and Career Preparation for Learner with Disabilities in Special Schools - Ahsan Romadlon Junaidi; Muhammad Irvan; Ediyanto Ediyanto; Asep Sunandar (PSIKOPEDAGOGIA Jurnal Bimbingan dan Konseling, 2022)
This study aimed to determine the differences between the career development of students with disabilities in private and public schools. It applied a comparative method involving 84 special education teachers teaching vocational education at the junior and senior high school levels. Career development was examined through the development perspective using three components: career awareness, exploration, and preparation. The first instrument was used to collect the demographic data, and the second instrument generated the teachers' perception of the career development of students with disability in the special schools. The obtained data were analyzed using the Kruskal-Wallis test. Our finding suggested that the career development of students with disabilities in private and public schools was not substantially different. Meanwhile, their career development based on their various disabilities also did not vary significantly. Interestingly, the students with intellectual disabilities presented narrower career development than those with other disabilities, primarily in the career preparation aspect. Our analysis showed that this finding could be caused by more significant hindrances encountered by the students with intellectual disabilities in relation to their self-determination. This research can be used as a basis for providing career services for the career development of students with special needs, both in private and public schools.